Some thoughts on the irrigation problem - McCauley, Charles Dwin (My University, 1896)
Introduction: From the earliest dawn of history, irrigation has played a very important part in furnishing man with the necessities of life. The Oriental Countries depended almost entirely on this method for supplying their crops with water. The phenomenal fertility of the Valley of the Nile is a wonder to the people of all nations. It, however, is not any more productive than the now bleak and barren fields along the Euphrates were when Nineveh and Babylon were at the zenith of their glory.
Citation: McCauley, Charles Dwin. Some thoughts on the irrigation problem. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: History; Irrigation; Oriental countries; Theses; Manuscripts (documents)